Future of Video Streaming Platforms and Mainstream Cinema: A Case Study of Fujian Province, China - Yaqoub, Muhammad (Journal of Peace, Development and Communication, 2022)
The pandemic has dramatically changed the current film-viewing landscape from cinema theatres to streaming services. Video streaming platforms (VSPs) are hailed as the future of the Chinese Film & Entertainment industry. The potential viewers for the digital video platforms are about to skyrocket during coronavirus and beyond. The COVID protocols, such as biometric surveillance and quarantine-driven isolation after a COVID scare, forced the cinema-goers to stay safe at home and enjoy the films, web series, and shows. In the time of streaming services, the cinema theatre is grappling with doing business. This study explores post-pandemic prospects, explaining why movie-lovers access and prefer to video streaming services and how these digital platforms are replacing big screens. The study reveals that most respondents use the VSPs on their smartphones and laptops to watch films. These platforms distrust the cinema-goers to visit the cinema to watch the films even though they do not think that the future is only on video streaming platforms. Easy to access, various genres, cheaper, and user-friendly factors make VSPs popular among the audience. After the post-lockdown period, the cinema industry needs to rethink and develop tactics to attract and keep the youth frequently visit the cinema.